2022
DOI: 10.3389/fimmu.2022.796542
|View full text |Cite
|
Sign up to set email alerts
|

Danggui-Shaoyao-San Attenuates Cognitive Impairment via the Microbiota–Gut–Brain Axis With Regulation of Lipid Metabolism in Scopolamine-Induced Amnesia

Abstract: Danggui-Shaoyao-San (DSS) has a long history of being used as a traditional medicine (TCM) and has been reported to show therapeutic effects in alleviating the symptoms of cognitive impairment. The purpose of this study was to investigate whether DSS treatment attenuates cognitive impairment via the microbiota–gut–brain axis in scopolamine-induced amnesia. In this work, we first performed the Morris water maze (MWM) test and novel object recognition (NOR) test to evaluate the memory function of treated C57BL/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…In this study, we reported that DSS regulates a variety of metabolic pathways including PPAR signaling pathway. Consistently, Liu et al (2022) also demonstrated that DSS regulates lipid metabolism though PPARG in scopolamineinduced amnesia. These findings indicated that DSS may play a reno-protective role in DKD through metabolism pathways by targeting PPARG, which is worthy to be validated by experiments in the future.…”
Section: Discussionsupporting
confidence: 58%
“…In this study, we reported that DSS regulates a variety of metabolic pathways including PPAR signaling pathway. Consistently, Liu et al (2022) also demonstrated that DSS regulates lipid metabolism though PPARG in scopolamineinduced amnesia. These findings indicated that DSS may play a reno-protective role in DKD through metabolism pathways by targeting PPARG, which is worthy to be validated by experiments in the future.…”
Section: Discussionsupporting
confidence: 58%
“…Scopolamine injections have been demonstrated to positively correlate with Clostridium, Bifidobacterium, Ruminococcaceae_unclassified, Lachnospiraceae_unclassified, and Lactobacillus while being negatively related to Desulfovibrio, Akkermansia , and Blautia [ 23 ]. Scopolamine injections increase the intestinal permeability and induce memory impairment [ 23 , 24 ]. The present study also showed similar changes in the gut microbiota and memory function.…”
Section: Discussionmentioning
confidence: 99%
“…The primary gut bacteria in the different groups can be determined by LDA, which identifies the bacteria that are more abundant in one group than another, adopting a principle of analysis closely related to the principal component analysis and linear regression analysis [ 24 ]. The present study demonstrated that only Escherichia was selected with a high LDA score in the AD group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, antimicrobial therapy, as used in the prevention and treatment of AD, induces the suppression of pro-inflammatory cytokines and Aβ aggregation. Treatment with DSS and HLJDD attenuated cognitive impairment through their actions on the microbiome-gut-brain axis, such as reduced alterations in the gut microbiome ( Gu et al, 2021 ; Liu et al, 2022 ). In addition, Gu et al (2021) indicated that the combination of inflammatory cytokines (interleukin-6 and interferon-gamma), phosphatidylcholines, and SCFA-producing bacteria were expected to be early diagnostic biomarkers for AD.…”
Section: Preclinical Studies Of Herbal Medicine Based On the Holistic...mentioning
confidence: 99%